Spin-polarized current generation and detection by a double quantum dot structure - Dahlhaus, Jan; Maier, Stefan; Komnik, Andreas (Physical review. B, Condensed matter and materials physics, 2010)
We propose a device acting as a spin valve which is based on a double quantum dot structure with parallel topology. Using the exact analytical solution for the noninteracting case we argue that, at a certain constellation of system parameters and externally applied fields, the electric current through the constriction can become almost fully spin polarized. We discuss the influence of the coupling asymmetry, finite temperatures, and interactions on the efficiency of the device and make predictions for the experimental realization of the effect.